2018
DOI: 10.1038/s41419-018-0604-z
|View full text |Cite
|
Sign up to set email alerts
|

The novel 19q13 KRAB zinc-finger tumour suppressor ZNF382 is frequently methylated in oesophageal squamous cell carcinoma and antagonises Wnt/β-catenin signalling

Abstract: Zinc finger proteins (ZFPs) are the largest transcription factor family in mammals. About one-third of ZFPs are Krüppel-associated box domain (KRAB)-ZFPs and involved in the regulation of cell differentiation/proliferation/apoptosis and neoplastic transformation. We recently identified ZNF382 as a novel KRAB-ZFP epigenetically inactivated in multiple cancers due to frequent promoter CpG methylation. However, its epigenetic alterations, biological functions/mechanism and clinical significance in oesophageal squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…In support of this hypothesis, we identified increased H3K27me3 levels at the promoter of many of the H3K27me-depedent migration-repressed genes, such as Rassf7 , Zfp382 , and Tciam ( Figure 5 d–f). Interestingly, Rassf7 was shown to inhibit the MKK7/JNK signaling pathway [ 63 ], Zfp382 was shown to inhibit the transcription of various tumor and migration promoting genes [ 64 , 65 ], and Tciam was found to inhibit LPS signaling and NF-κB activity [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, we identified increased H3K27me3 levels at the promoter of many of the H3K27me-depedent migration-repressed genes, such as Rassf7 , Zfp382 , and Tciam ( Figure 5 d–f). Interestingly, Rassf7 was shown to inhibit the MKK7/JNK signaling pathway [ 63 ], Zfp382 was shown to inhibit the transcription of various tumor and migration promoting genes [ 64 , 65 ], and Tciam was found to inhibit LPS signaling and NF-κB activity [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…We thus investigated the functions of ZNF471 in breast cancer. Previous studies have shown that KRAB-ZFPs are associated with cancer cell proliferation and are important for other biological functions, including apoptosis and migration/invasion in several tumors [ 21 , 23 , 33 ]. Therefore, the tumor-suppressive functions of ZNF471 in breast cancer were first investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…ZNF382 also inhibited the proliferation and metastasis of ESCC cells by inhibiting the Wnt/beta-catenin signaling pathway. These data suggest that ZNF382 plays a role in inhibiting the formation of ESCCs [ 18 ]. ZNF382 is also methylated in a range of primary tumors (nasopharyngeal, esophageal, colon, stomach, and breast).…”
Section: Discussionmentioning
confidence: 99%